Comparison of the effects of general, spinal and epidural anesthesia on ureter access and surgical outcomes during flexible ureterorenoscopy for transurethral single stone removal surgeries: a monocentric retrospective study. (1st January 2021) - Cai, Haoliang; Wu, Xiaohui; Chen, Xi; Chen, Wenting
Abstract: Background: In ureterorenoscopy, anaesthesiologists are preferring regional anaesthesia to avoid postoperative complications, while surgeons are preferring general anaesthesia to avoid ureteral trauma. China has not published its guidelines and not referring to the European Association of Urology guidelines. The objectives of study were to evaluate the effects of general, spinal, and epidural anaesthesia on ureter access and surgical outcomes of ureterorenoscopy. Methods: Charts of a total of 392 patients with the American Society of Anaesthesiologists grade I or II, and underwent flexible ureterorenoscopy for removal of the proximal, middle, or distal ureteral single stone under general anaesthesia (GA group; n  = 145) or spinal anaesthesia (SA group; n  = 131) or epidural anaesthesia (EA group; n  = 116) were reviewed retrospectively. Results: The dilatation time for patients of GA group was fewer than those of SA (104.01 ± 12.77 sec/patient vs. 130.55 ± 22.53 sec/patient, p  < .0001, q  = 17.0350) and EA (104.01 ± 12.77 sec/patient vs. 147.03 ± 18.76 sec/patient, p  < .0001, q  = 26.7240) groups. The time to reach to stone for patients of GA group was fewer than those of SA (126.68 ± 12.59 sec/patient vs. 137.60 ± 17.84 sec/patient, p  < .0001, q  = 8.4510) and EA (126.68 ± 12.59 sec/patient vs. 149.44 ± 14.85 sec/patient, p  < .0001, q  = 17.0350) groups. The lithotripsy time ( p  = .359), operation time ( p  = .449), intraoperative complications ( p  = .058), and length of hospital stays ( p  = .057) of patients were same among groups. Visual analog scale pain scores of patients of the GA group found higher among groups. General anaesthesia caused nausea and vomiting. Conclusions: This study suggests general anaesthesia for flexible ureterorenoscopy if there is no contraindication. KEY MESSAGE: General anaesthesia facilitates early dilatation of ureters and access to the stone. No strong correlation of the anaesthesia method of choice with lithotripsy time, operation time, intraoperative complications, stone-free conditions, and length of hospital stays. Epidural and spinal anaesthesia have advantages of fewer postoperative pain and better postoperative outcomes for flexible ureterorenoscopy.